EFFORTS TO PRESERVE A DATA MOPOLIHU LO LIMU (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Adat is one of the regulations that govern human life . Adat was first recognized by someone from the family environment, then expanded to become part of society. Furthermore, in an effort to develop national culture, one of the efforts made by the Indonesian government is an attempt to explore and develop the largest customs in various regions, one of which is the Mopolihu Lo Limu tradition found in the Gorontalo community.